2014
DOI: 10.1016/j.jcps.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Strategic benefits of low fit brand extensions: When and why?

Abstract: Brand extensions have the potential to both enhance liking of the brand extension and induce positive spillover effects on the parent brand. Such dual outcomes enhance the brand's growth potential. We propose and empirically demonstrate that three variables endemic to any brand extension decision (brand reputation, brand extension fit, brand extension benefit innovativeness) jointly impact these positive outcomes. For strong reputation brands, these dual outcomes are maximized when the brand extension is low i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…Current marketing practice has been favoring meaningful names for branding since they are easier to remember and seem to induce more positive affect than nonmeaningful names (Klink, ). Nevertheless, since companies’ portfolios are growing, brand names are required to become more permeable and adaptable to several products (see Chun, Park, Eisingerich, & MacInnis, , for a discussion of the variables affecting successful brand extensions). In other words, establishing a particular connection between the name and the product is increasingly difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Current marketing practice has been favoring meaningful names for branding since they are easier to remember and seem to induce more positive affect than nonmeaningful names (Klink, ). Nevertheless, since companies’ portfolios are growing, brand names are required to become more permeable and adaptable to several products (see Chun, Park, Eisingerich, & MacInnis, , for a discussion of the variables affecting successful brand extensions). In other words, establishing a particular connection between the name and the product is increasingly difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research further confirmed the theory by Chun et al (2015) when the results demonstrated that innovativeness was an absolutely significant predictor for brands entering into cross-category markets. This attribute established a consumer attitude toward an iconic product because innovativeness positively affected their acceptance of the cross-category extension and eliminated the "incongruity feeling": The degree to which consumers felt innovativeness in the extension was the same degree to which the consumer was willing to accept the extension product, as it was congruent with the iconic product.…”
Section: Sample Descriptionsupporting
confidence: 83%
“…There is empirical evidence for people getting instantaneously attached to digital services they use [ 54 ]. This can be because of an appealing interface, use of logos [ 55 ], the ethical standards of the service offering [ 56 ], or the versatility of the functional benefits provided [ 57 ]. Which social platform can medical students identify with based on the various benefits these platforms have to offer and their identification with work [ 58 ]?…”
Section: Discussionmentioning
confidence: 99%